The relationship between personality and motivation - Sukuvaara, Sofia (My University, 2015)
Despite motivation‘s crucial role in every human’s action, the relationship between personality and motivation has been little researched in the science world. It has suggested that individual differences may play an important role in the success of motivation theories. Therefore, this study investigates whether there is a relationship between motivation and personality. The most influential and best-known personality theories are Freud’s, Jung’s and the Big Five theory. The Myers-Brigg Indicator has also gained popularity as a personality tool for organizational development and management. Fundamental theories in the motivation field are Maslow’s and McClelland’s need theories, Equity, Expectancy and Self-Efficacy theories. Also Two-Factor theory and Motivation Sources Inventory are widely recognized. Theoretical base for this study is formed from the Myers-Briggs Indicator and Motivation Sources Inventory. The empirical analysis was made with qualitative research. Six participants representing distinct MBTI personality types completed a questionnaire based on Motivation Sources Inventory. The questionnaire included 16 semi-structured questions. The responses were analyzed by seeking typical expressions, which could be done by each MBTI preference. Only a few significant relations were found between MBTI preferences and motivation. The conclusion of the study is that motivation and personality appear to be distinct concepts. The study confirms the similar results of the previous studies done in the field. Therefore, motivation sources can not be reliably predicted from the MBTI- preferences.
Keywords: Personality; Motivation; MBTI; Motivation Sources Inventory; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|